Operations and maintenance performance in production and manufacturing assets - Liyanage, Jayantha P (Journal of manufacturing technology management, 2007)
Purpose - Sustainable production and manufacturing is an emerging concept for commercially successful performance. A question is how core asset processes should be streamlined to ensure performance quality and to portray their business roles within sustainability requirements. The purpose of this paper is to address this issue from asset operations and maintenance (O&M) perspective.Design methodology approach - Issues discussed here are based on findings from a project launched during 2000-2003 in Norway with major emphasis on performance integrity, consistency, and quality.Findings - Through the findings of the original study, the paper elaborates on the important "Business - Production or Manufacturing asset - Operations and Maintenance" performance architecture in sustainable business environments.Research limitations implications - The paper aims at stimulating production and manufacturing cluster to initiate joint R&D efforts to further explore and research this interesting and important subject matter that seems to be sensitive from socio-economical viewpoint.Practical implications - The paper provides a framework to explore and specify critical elements for a risk-based industrial asset management practice in dynamic and complex settings of sustainable environments. This is critical for many commercial businesses with the ongoing debates on the proper balance between profits and fundamentals, and to develop effective performance measurements and auditing systems for asset O&M process to ensure integrity, consistency and quality in performance.Originality value - Many underlying issues regarding sustainability performance in production and manufacturing environments still remain ill-defined. This paper clarifies how the emerging sustainable business concept can influence performance in industrial production and manufacturing assets, and how to outline a framework to streamline O&M performance.